Taxonomy and reclassification of South African Asteraceae genus Elytropappus (Gnaphalieae, Asteraceae), the description of two new genera and two new species - Koekemoer, Marinda (Phytotaxa, 2019)
This revision of the genus Elytropappus confirms earlier views that there are three distinct groups represented in the genus. This paper formalizes the three groups and describes two new genera, as well as two new species identified during the study. Dicerothamnus is described for D. rhinocerotis and D. adpressus, and Myrovernix for M. longifolius, M. intricata, M. gnaphaloides, M. scaber and M. glandulosus. In the original genus (including the type species, Elytropappus hispidus), two new species, Elytropappus aridus and E. monticola, are described. Morphological characters supporting this new classification are discussed and illustrated.